An Analysis of Public Transit Connectivity Index in Tehran. The Case Study: Tehran Multi-Modal Transit Network - Mamdoohi, Amir Reza; Zarei, Hamid (TeMA - Journal of Land Use, Mobility and Environment, 2016)
Public transit is a major priority in modern management of large cities and metropolitan areas in particular. Public transit systems in such cities consist of a large number of nodes and lines which are represented by a complex network. A station for public transit is a bridge between the people and public transit network, based on which, the concept of input and output power for each station can be defined. The objective of this study is the application of the transit connectivity indices to the multimodal transit network in the city of Tehran. The public transit network data employed in this study is taken from Tehran Traffic Control Company, and Tehran Urban and Suburban Railway Operation Company. The methodology for measuring transit connectivity consists of three measures: Node connectivity, Line connectivity and Regional connectivity, where activity density is applied to these measures. The results of node connectivity analysis shows that most of the node connectivity in concentrated in the city center with many nodes in the center along routes going north and south. The line connectivity analysis shows that there is a concentration of highly connected lines that are near Tehran municipality region 12 and 16. Finally, we find that areas with more metro and bus facilities with respect to the other areas, have a better regional connectivity. One of these areas includes Sadeghiyeh Metro Station which is the junction of Tehran Metro Line 2 and Tehran Metro Line 5 which have a high connectivity power. Results of this study can be used to suggest some ideas on how future investments in rail and bus should be prioritized. Particularly in Transit Oriented Development (TOD) and sustainble development projects, urban planners can design transit stations with high performance to access the crucial services in poor areas.